Brand Awareness Moderation on Customer Loyalty in Culinary Business: Pengaruh Kesadaran Merek terhadap Loyalitas Pelanggan dalam Bisnis Kuliner - Putri Purnama Sari Dewi; Sriyono; Hadiah Fitriyah; Wisnu Panggah (Indonesian Journal of Innovation Studies, 2025)
General Background: Customer loyalty is an essential factor in maintaining business sustainability within highly competitive culinary industries. Specific Background: Marketing strategy, product quality, and service quality are widely recognized as important determinants of customer loyalty, while brand awareness is considered a relevant factor in shaping consumer responses toward products and services. Knowledge Gap: Previous studies generally examined the direct relationship between marketing strategy, product quality, service quality, and customer loyalty, while limited attention has been given to the moderating role of brand awareness in strengthening these relationships within medium-scale culinary businesses. Aims: This study aims to analyze the relationships between marketing strategy, product quality, and service quality toward customer loyalty and to examine the moderating role of brand awareness in these relationships. Results: The findings indicate that marketing strategy, product quality, and service quality were significantly associated with customer loyalty both partially and simultaneously. Service quality emerged as the strongest factor associated with customer loyalty. Furthermore, brand awareness significantly moderated the relationships between marketing strategy, product quality, service quality, and customer loyalty. Novelty: This study highlights the moderating function of brand awareness in the relationship between marketing strategy, product quality, service quality, and customer loyalty within the culinary business sector using Moderated Regression Analysis (MRA). Implications: The findings provide practical insight for culinary businesses to strengthen customer loyalty through integrated marketing strategy, consistent product quality, service quality improvement, and continuous brand awareness development.Highlights: Service quality showed the strongest relationship with consumer retention behavior. Marketing activities and product standards were significantly associated with repeat purchase intention. Brand recognition strengthened the relationship between business variables and consumer commitment. Keywords: Customer Loyalty; Brand Awareness; Marketing Strategy; Product Quality; Service Quality